2019
DOI: 10.1021/acsami.8b21768
|View full text |Cite
|
Sign up to set email alerts
|

Upshift of the d Band Center toward the Fermi Level for Promoting Silver Ion Release, Bacteria Inactivation, and Wound Healing of Alloy Silver Nanoparticles

Abstract: Silver (Ag)-based nanoparticles (NPs) with a high potential of Ag+ release have been known to be capable of promoting bacteria inactivation and the wound healing process; however, keeping a steady flux of high levels of Ag+ in Ag-based NPs is still challenging. Herein, a novel strategy in terms of altering the intrinsic electronic structure of Ag NPs was attempted to facilitate Ag oxidation and boost the Ag+ flux, as results of improved antibacterial and wound healing performance of Ag NPs. Gold (Au), platinum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 36 publications
1
49
0
Order By: Relevance
“…This antimicrobial activity directly corresponded to the dissolution rates of ionic silver, as well as the particle morphology (specific surface area). Therefore, it can be suggested that the antimicrobial efficacy of Pt‐AgNPs can be ascribed to the rapidly released silver ions due to the specific surface areas associated with the morphology of the nanoparticles (Breisch et al, 2019; Chang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This antimicrobial activity directly corresponded to the dissolution rates of ionic silver, as well as the particle morphology (specific surface area). Therefore, it can be suggested that the antimicrobial efficacy of Pt‐AgNPs can be ascribed to the rapidly released silver ions due to the specific surface areas associated with the morphology of the nanoparticles (Breisch et al, 2019; Chang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, alloying with platinum did not enhance the antimicrobial activity of silver nanoparticles. However, it should be noted that platinum concentrations lower than 10 mol% were not investigated in these studies (Breisch et al, 2019; Chang et al, 2019).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The desired attributes of the product granules are controlled by the feed powder, liquid properties, type of granulator and the operating parameters. In the last 50 years, granulation has been widely used in specialty chemicals, pharmaceuticals, mineral processing, agricultural products and food 21‐23 . If the Li 2 O powder can be directly prepared into a uniform sphere by wet granulation, it will be of great significance for the development of the breeder blankets.…”
Section: Introductionmentioning
confidence: 99%